Oxidative Stress: Molecular Mechanisms, Role in Pathology, and Therapeutic Implications - Martindah, Eny; Khairullah, Aswin Rafif; Widiastuti, Raphaella; Andriani, Andriani; Damayanti, Rini; Mustofa, Imam; Mulyati, Sri; Sukmanadi, Mohammad; Wardhani, Bantari Wisynu Kusuma; Ahmad, Riza Zainuddin; Akintunde, Adeyinka Oye; Pratama, Bima Putra; et al. (Trends in Sciences, 2025)
Oxidative stress is a biological state caused by an imbalance between the generation of reactive oxygen species (ROS) and the antioxidant system’s capacity to maintain redox homeostasis. This imbalance can damage vital biomolecules, including proteins, lipids, and DNA, and can initiate cellular signaling pathways involved in metabolic dysfunction, inflammation, and apoptosis. ROS originate from various endogenous sources, such as mitochondria and oxidase enzymes, as well as exogenous factors like pollution, radiation, and heavy metals. This article provides a comprehensive review of the molecular mechanisms of oxidative stress, covering ROS types, biomolecular damage pathways, and the activation of redox-sensitive signals such as Nrf2, NF-κB, and MAPK. Cellular defense mechanisms against ROS, including enzymatic and non-enzymatic antioxidant systems, are also described. Oxidative stress is implicated in numerous chronic diseases, including neurological disorders, cardiovascular disease, diabetes mellitus, cancer, infertility, liver disease, and aging. Therapeutic strategies studied to counteract oxidative stress include redox-sensitive pharmaceuticals, lifestyle modifications, and antioxidant supplementation. Despite extensive research, antioxidant supplementation in clinical trials has produced inconsistent results, and in some cases, excessive intake has been associated with adverse effects, underscoring the complexity of modulating oxidative stress in therapy. Ongoing issues and debates persist regarding clinical efficacy, the risks of over-supplementation, and the need for personalized treatment approaches. This review also highlights potential future research directions, including the development of tailored interventions based on individual redox status and the use of oxidative stress biomarkers as more precise tools for therapeutic and diagnostic evaluation. HIGHLIGHTS Provides a comprehensive overview of the molecular mechanisms of oxidative stress, including ROS sources, ROS and RNS types, and related redox signaling pathways. Explores the role of oxidative stress in the pathogenesis of chronic diseases such as cancer, diabetes mellitus, cardiovascular, neurodegenerative disorders, infertility, liver disease, and aging. Describes the antioxidant defense system, both enzymatic and non-enzymatic, including genetic regulation through the Nrf2–Keap1 pathway. Discusses therapeutic interventions including antioxidant supplementation, pharmacological approaches, and lifestyle modifications to address redox imbalance. Identifies current challenges, controversies, and future research directions in oxidative stress management, emphasizing the need for personalized therapies based on individual redox status. GRAPHICAL ABSTRACT